THE KSPPS STRATEGY OF BMT AIRLANGGA WAS DEVOTED TO PERSADA DURING THE COVID-19 PANDEMIC - Muhammad Deni Putra; Faishol Luthfi; Wildana Latif M (Imara: JURNAL RISET EKONOMI ISLAM, 2021)
The Covid-19 pandemic has affected many aspects. Not only for MSMEs but also Islamic microfinanceinstitutions. This study aims to determine the strategy of Islamic microfinance institutions, namely KSPPS BMTAirlangga Bakti Persada during the Covid-19 pandemic. This research uses a descriptive qualitative approachwith a case study method. The results of this study indicate that KSPPS BMT Airlangga Bakti Persada has acertain strategy so that it can survive in the Covid-19 pandemic era. The strategy includes risk managementand operational management at the institution. Risk management includes the management of default riskby members and management of default risk by the institution. Operational management is related to healthprotocols so that employees are not exposed to the Covid-19 virus.